Perancangan Sistem Informasi Pemantauan Proyek Kerja Berbasis Website Di PT. XYZ - Wijaya, Masesa Angga; Perdana, Chepy; Rofiani, Riska (LPPM Universitas Nias Raya, 2024)
The purpose of this research is to design a project monitoring system at PT. XYZ. The company faces several challenges, including difficulties for Project Managers and clients to obtain information from production employees regarding the progress of their work, and the lack of proper income reporting. This design is expected to help the company get information about the progress of work completed by production employees and to record advance payments and final payments for a project. The methodology used in this research is the waterfall methodology, which includes the stages of requirement, design, implementation, verification, and maintenance. However, the author only uses two stages: requirement and design. In the design stage, the modeling of the system uses Unified modeling language (UML) diagrams, consisting of use case diagram, activity diagram, sequence diagram, and class diagram. For database design, the entity relationship diagram (erd) is used. To create the user interface (ui/ux) design, figma is used to facilitate the system design process. The results of this research include a design with three main features: Project Managers can monitor the progress of production employees' work, clients can monitor the progress of the projects they have submitted, and advance payments and final payments for a project can be recorded. The recommendation is to develop this design into a mobile-based application to make it more effective and efficient, and to add a feature for direct payment within the app for advance payments and final payments for a project.